2011
DOI: 10.2478/v10007-011-0017-3
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and evaluation of mucoadhesive glipizide films

Abstract: Glipizide is mainly absorbed in the proximal areas of the gastrointestinal tract. The purpose of this study was formulation and evaluation of mucoadhesive films to prolong the stay of drug in its absorption area. Glipizide was formulated in a mucoadhesive film that could be retained in the stomach for prolonged intervals. Polymeric films were designed with various compositions of hydroxypropyl cellulose and polyethylene glycol 400 (PEG 400). Properties of the mucoadhesive film such as tensile strength, percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 15 publications
3
5
0
Order By: Relevance
“…The increase of PG concentration led to significant decrease in the swelling index which can be attributed to the interaction of PG with the hydrophilic polymers (HPMC and PVA) via hydrogen bonding and this decreases the effective water uptake by the polymers, thus reducing the swelling of the films (Sanyang et al., 2016 ). Decrease in swelling due to the increase in the plasticizer concentration was reported in previous studies (Müller et al., 2008 ; Rajput et al., 2011 ).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The increase of PG concentration led to significant decrease in the swelling index which can be attributed to the interaction of PG with the hydrophilic polymers (HPMC and PVA) via hydrogen bonding and this decreases the effective water uptake by the polymers, thus reducing the swelling of the films (Sanyang et al., 2016 ). Decrease in swelling due to the increase in the plasticizer concentration was reported in previous studies (Müller et al., 2008 ; Rajput et al., 2011 ).…”
Section: Resultssupporting
confidence: 73%
“…It was observed that increasing the concentration of PG from 10% to 30% led to decrease in mucoadhesion force of the prepared films (Rajput et al., 2011 ) which can be explained that PG contain hydroxyl (OH) groups that can form effective hydrogen bonding with both mucin and hydrophilic polymers such as HPMC and PVA, thus weakening the effective bonding between the polymer and mucin with the consequent decrease in mucoadhesion (Rajput et al., 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ratio of increased length of the film to original length is calculated for elongation at break. Using a higher concentration of plasticizer resulted in lower tensile strength values, which is compatible with literature (20). Hydrophilicity and wettability of the films were evaluated by contact angle measurements.…”
Section: Discussionsupporting
confidence: 86%
“…The addition of Lycoat RS720 polymer to both 3% and 4% sodium alginate does not result in an increase of mucoadhesion strength ( p ≥ 0.05) (S3 Table). Previous studies have reported an optimum mucoadhesive strength of 0.39±0.01 N which is close to the mucoadhesive strength of the F15 formulation (Table 3) [12]. Interestingly, addition of Lycoat RS720 also demonstrated a significant increase in percentage of elongation in both 3% and 4% sodium alginate formulations where p-value less than 0.05 (S3 Table).…”
Section: Resultssupporting
confidence: 69%